(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Disability is a major throwback in developing countries like India. The data showed a decade back that diseases associated with virus such as Polio will have to be eradicated with global alarm to regulate and fight with such deadly viruses which are responsible in ruining the lives of people who are not so aware of such diseases. There are different issues in different countries and conservation or rehabilitation measures are also different in most of the countries that varies with land, poverty, education and mass contribution to combat such problems. In India, due to lack of education and awareness such diseases and problems got areas to stretch their arms. Researchers were keen to find solutions to such problems and faced troubles in covering the wide areas and taking aid from government authorities and NGO’s to overcome such issues. With the help of this research paper, scope and major issues, challenges concerning disability and rehab measures in India are being tried to discussed upon and adoptive measures regarding health care for disabled in the community.